The Role of Chlorella vulgaris in Reducing Some Pharmaceutical Wastes Toxicity in Clam Pseudodontopsis euphraticus (Baghdad Science Journal, 2024)
Applications of microalgae in environmental studies have recently increased. Current uses of immobilized microalga Chlorella vulgaris include reducing pharmaceutical substances such as amoxicillin AMX and potassium dichromate K2Cr2O7 on freshwater clam Pseudodontopsis euphraticus as a biotic model. Recent research pointed out a change in biomarkers of oxidative stress in an evaluation of induced toxicity. Where clams were exposed to different concentrations100, 200, and 400 mg/L for 7 days and 20, 30, and 50 mg/L for 5 days of amoxicillin and potassium dichromate, respectively. The results showed that exposure to AMX and K2Cr2O7 led to a significant change in the activity of antioxidant enzymes, with significant increases (p<0.05) in reactive oxygen species (ROS) production. The highest ROS value was 51.05 μg/mg under concentrations of 50 mg/L of K2Cr2O7, and the highest recorded percentage of Superoxide Dismutase SOD, Catalase CAT, Malondialdehyde MDA, and Glutathione Reductase GSH, as: 33.40 U/m, 33.32KU/L, 23.22 μmol/l and 21.30µg/g respectively, in concentrations of 50 mg/L of K2Cr2O7 non-treated. It was observed in this study that potassium dichromate was more effective than amoxicillin in causing toxicity. According to the current study, immobilized C. vulgaris was instrumental in decreasing chemicals toxicity, by relieving oxidative stress on P. euphraticus clam, as it recorded a significant decrease p≤ 0.05 in ROS values and oxidizing enzymes such as Superoxide Dismutase SOD, Catalase CAT, Malondialdehyde MDA, as well as ascorbic acid. AA, total protein and GPX in treated samples.